2014
DOI: 10.1002/jcp.24521
|View full text |Cite
|
Sign up to set email alerts
|

MEK1/2 Overactivation Can Promote Growth Arrest by Mediating ERK1/2-Dependent Phosphorylation of p70S6K

Abstract: The extracellular signal-regulated kinase (ERK)1/2 mitogen-activated protein (MAP) kinase pathway has been involved in the positive and negative regulation of cell proliferation. Upon mitogen stimulation, ERK1/ERK2 activation is necessary for G1- to S-phase progression whereas when hyperactived, this pathway could elicit cell cycle arrest. The mechanisms involved are not fully elucidated but a kinase-independent function of ERK1/2 has been evidenced in the MAPK-induced growth arrest. Here, we show that p70S6K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 72 publications
3
30
0
Order By: Relevance
“…MEK1 and MEK2 are >86% identical at the amino acid level and evaluation of their constitutively active mutants has revealed functional redundancy in a large extent of cell physiology [15, 34–36], although MEK1 and MEK2 can exhibit distinct physical interactions with certain proteins, e.g., A-Raf [37] and the scaffold MP1 [38]. In the context of p21 CIP1 regulation, we and others previously showed that overexpression of constitutively active MEK1 or MEK2 mutants was equally effective for inducing p21 CIP1 expression in LNCaP and other cell lines [15, 36]. Therefore, it is hardly conceivable that the differential effects of MEK1 and MEK2 knockdown on p21 CIP1 mRNA levels represent distinct intrinsic properties of MEK1 and MEK2.…”
Section: Discussionmentioning
confidence: 99%
“…MEK1 and MEK2 are >86% identical at the amino acid level and evaluation of their constitutively active mutants has revealed functional redundancy in a large extent of cell physiology [15, 34–36], although MEK1 and MEK2 can exhibit distinct physical interactions with certain proteins, e.g., A-Raf [37] and the scaffold MP1 [38]. In the context of p21 CIP1 regulation, we and others previously showed that overexpression of constitutively active MEK1 or MEK2 mutants was equally effective for inducing p21 CIP1 expression in LNCaP and other cell lines [15, 36]. Therefore, it is hardly conceivable that the differential effects of MEK1 and MEK2 knockdown on p21 CIP1 mRNA levels represent distinct intrinsic properties of MEK1 and MEK2.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that expression of constitutively active Ras, Raf, or MEK mutants could induce irreversible growth arrest in different malignant tumor cells which were not transformed by Ras or Raf. These cell lines were derived from diverse tumor types, including small cell lung carcinoma (Mabry et al, 1989; Ravi et al, 1998, 1999a), medullary thyroid carcinoma (MTC) (Nakagawa et al, 1987; Carson et al, 1995; Carson-Walter et al, 1998; Park et al, 2003; Vaccaro et al, 2006), glioma (Fanton et al, 2001), pheochromocytoma (Wood et al, 1993; Park et al, 2005b), gastrointestinal carcinoid (Sippel et al, 2003), prostate carcinoma (Ravi et al, 1999b; Hong et al, 2011), hepatocarcinoma (Guégan et al, 2013b) and breast carcinoma (Taylor et al, 2011). In some of these tumor cell lines, Raf/MEK/ERK activation could lead to expression of senescence-associated β-galactosidase (Ravi et al, 1999b; Arthan et al, 2010; Taylor et al, 2011), a key marker used for senescence determination (Gupta and Wajapeyee, 2013).…”
Section: Cell Types In Which Aberrant Raf/mek/erk Activation Can Imentioning
confidence: 99%
“…Gene deletion in mice also revealed a critical difference in their requirement at an early developmental stage (Giroux et al, 1999; Bélanger et al, 2003; Nadeau et al, 2009). Further, their unique functions in epidermal neoplasia or hepatocarcinoma growth have been reported (Scholl et al, 2009; Guégan et al, 2013b), although activation of MEK1 or MEK2 was equally sufficient to transform intestinal epithelial cells and to induce the formation of metastatic tumors (Voisin et al, 2008). It is noteworthy that determination of functional specificity of MEK1 and MEK2 can be affected by their intrinsic properties as well as gene dosage effects.…”
Section: The Role Of Raf Mek1/2 and Erk1/2 In Growth Arrest Signmentioning
confidence: 99%
See 2 more Smart Citations